User-friendly nonlinear nonparametric estimation framework for vibro-acoustic industrial measurements with multiple inputs. (November 2020) - Csurcsia, Péter Zoltán; Peeters, Bart; Schoukens, Johan
Highlights: User-friendly estimation method for industrial measurement with multiple inputs. Automated processing of measurement data. Nonparametric nonlinearity assessment for large scale systems. Automatic transient removal of nonparametric model. Methods applied and verified on real-life measurements. Abstract: This paper introduces a user-friendly estimation framework for industrial measurements of vibro-acoustic systems with multiple inputs. Many mechanical structures are inherently nonlinear and there is no unique solution for modeling nonlinear systems. This is especially true when multiple-input, multiple-output (MIMO) systems are considered. This paper addresses the questions related to the user-friendly semi-automatic processing of MIMO measurements with respect to the design of experiment and the analysis of the measured data. When the proposed framework is used, with a minimal user interaction, it is easily possible a) to decide, if the underlying system is linear or not, b) to decide if the linear framework is still accurate (safe) enough to be used, and c) to tell the inexperienced (non-expert) user how much can be gained using an advanced nonlinear framework. The proposed nonparametric industrial framework is illustrated on various real-life measurements.